New Work Forms: How to Integrate Them in Our Social Insurances - Saskia Montebovi; Alberto Barrio Fernandez; Paul Schoukens (Wirtschaftsdienst, 2020)
The increase in the group of atypical workers means that their social security protection needs reviewing. How far should we go in approaching social security for self-employed workers, flex workers, crowd workers and all new employment relationships differently? This will depend on the number of elements in respect to which the atypical employment relationship differs from the established standard: the full-time employee with a permanent employment contract. What we propose is a social security system that is sufficiently flexible in its implementation to give the different groups of workers an equal place and at the same time maintain a financially sustainable social security system providing sufficient social security protection for typical and atypical workers.
Keywords: J21; J28; O39; 330